Correlates of sedentary time in different age groups: results from a large cross sectional Dutch survey. (December 2016) - Bernaards, Claire; Hildebrandt, Vincent; Hendriksen, Ingrid
Abstract Background Evidence shows that prolonged sitting is associated with an increased risk of mortality, independent of physical activity (PA). The aim of the study was to identify correlates of sedentary time (ST) in different age groups and day types (i.e. school-/work day versus non-school-/non-work day). Methods The study sample consisted of 1895 Dutch children (4–11 years), 1131 adolescents (12–17 years), 8003 adults (18–64 years) and 1569 elderly (65 years and older) who enrolled in the Dutch continuous national survey 'Injuries and Physical Activity in the Netherlands' between 2006 and 2011. Respondents estimated the number of sitting hours during a regular school-/workday and a regular non-school/non-work day. Multiple linear regression analyses on cross-sectional data were used to identify correlates of ST. Results Significant positive associations with ST were observed for: higher age (4-to-17-year-olds and elderly), male gender (adults), overweight (children), higher education (adults ≥ 30 years), urban environment (adults), chronic disease (adults ≥ 30 years), sedentary work (adults), not meeting the moderate to vigorous PA (MVPA) guideline (children and adults ≥ 30 years) and not meeting the vigorous PA (VPA) guideline (4-to-17-year-olds). Correlates of ST that significantly differed between day types were working hours and meeting the VPA guideline. More working hours were associated with more ST on school-/work days. In children and adolescents, meeting the VPA guideline was associated with less ST on non-school/non-working days only. Conclusions This study provides new insights in the correlates of ST in different age groups and thus possibilities for interventions in these groups. Correlates of ST appear to differ between age groups and to a lesser degree between day types. This implies that interventions to reduce ST should be age specific. Longitudinal studies are needed to draw conclusions on causality of the relationship between identified correlates and ST.